2014
DOI: 10.1089/pho.2012.3439
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Movement in Orthodontic Treatment with Low-Level Laser Therapy: A Systematic Review of Human and Animal Studies

Abstract: Varying the wavelength with a reasonable dose in the target zone leads to obtaining the desired biological effect and achieving a reduction of the orthodontic treatment time, although there are studies that do not demonstrate any benefit according to their values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 31 publications
2
32
0
1
Order By: Relevance
“…In the current study, PBM-mediated biostimulatory effects were produced on the periodontal tissue, submitted to orthodontic tooth movement, in diabetic and normoglycemic rats, being similar to previous reports found in literature. 9,10,11,15 A recent review by Kim et al 13 suggest that the PBM used in orthodontics improves permeability of cell wall and influx of Ca ++ , enhances ATP production and collagen synthesis, increases pro-inflammatory and anti-inflammatory cytokines, as well as activates several proteolytic enzymes essential for extracellular matrix remodeling, PDL 50µm Figure 6. Representative immunohistochemical reactivity (arrows) for OPN in the 640J-LD group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, PBM-mediated biostimulatory effects were produced on the periodontal tissue, submitted to orthodontic tooth movement, in diabetic and normoglycemic rats, being similar to previous reports found in literature. 9,10,11,15 A recent review by Kim et al 13 suggest that the PBM used in orthodontics improves permeability of cell wall and influx of Ca ++ , enhances ATP production and collagen synthesis, increases pro-inflammatory and anti-inflammatory cytokines, as well as activates several proteolytic enzymes essential for extracellular matrix remodeling, PDL 50µm Figure 6. Representative immunohistochemical reactivity (arrows) for OPN in the 640J-LD group.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the photobiomodulation (PBM), previously known as low-level laser therapy (LLLT), has showed great effectiveness due to its analgesic, anti-inflammatory and photobiostimulatory properties, resulting in a faster tooth movement with no periodontal tissue side effects. 9,10,11,12,13,14,15,16,17 However, one of the key issues is to find an appropriate energy density for different experimental and clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…The relatively narrow wavelength range allows for greater absorption by target tissues. [8][9][10][11] Although both laser and LED are capable of delivering specific wavelengths at specific energy levels, they differ in several ways (Table 1). Lasers are spatially and temporally coherent, i.e., the light waves are identical in shape and size and travel together in the same space and time, thus permitting light to be focused.…”
Section: Photobiostimulation Modalitiesmentioning
confidence: 99%
“…9, 16-21 The rat model is the most commonly utilized animal but studies have also included monkeys, dogs, and cats. 8,22 Comparison among these studies has been rendered difficult due to the use of numerous different parameters between the studies ( Table 2) On the whole, the majority of the studies showed a positive effect of LLLT application (Table 2). Fold change appeared to be the most commonly used method for quantitating and comparing the amount of tooth movement.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Previous studies have examined periodontal tissue sections after experimental tooth migration, and the results suggest that LLLT enhances the expression of bone proteins . In addition, Cruz et al , Youssef et al , and Carvalho‐Lobato et al reported that the rate of retraction of the cuspid teeth of orthodontic patients increases with frequent (e.g., daily or every 2 days) low‐power diode laser irradiation.…”
Section: Introductionmentioning
confidence: 99%